Professional ethics of education inspection. A reflection on the ethical code of the AIEC from the philosophy of Paul Ricoeur - Giró París, Jordi (Avances en Supervisión Educativa, 2013)
The intent of this communication is twofold. On the one hand seeks to highlight the philosophy of Paul Ricoeur to a professional sector, the Education Inspectorate, which ignores ethical reflections on professions, in particular the references to physician and judicial order. And moreover submit an original and inspiring rereading the Code of Ethics of “Associació d’Inspectors d’Educació de Catalunya” (AIEC) from the deontological approach of hermeneutics and bioethics of Ricoeur.